Promoting equity through inclusive learning, planning and implementing: lessons from Nigeria's mass drug administration programme for neglected tropical diseases. (24th March 2023) - Piotrowski, Helen; Gwani, Noela; Yashiyi, James; Oluwole, Akinola; Ayuba, Samson; Surakat, Mobolanle; Adekeye, Oluwatosin; Lar, Luret; Kevin, Diltokka Gideon; Lawong, Bernsah Damian; Ntuen, Uduak; Islamiat, Soneye; et al.
Abstract: Background: An inclusive, localised approach to planning and implementing equitable mass drug administration was developed through participatory action research (PAR). This new approach aligns with principles of learning health systems (LHS). Tools were co-developed to support scaling up the new approach across two Nigerian states. Lessons are distilled here to enable learning for other programmes. Methods: Observations and reports by researchers (2019–2021) from 23 meetings and workshops, 8 in-depth interviews and 8 focus group discussions (FGDs) were used. Results: Nine key steps of best practice were identified to promote inclusive LHS for participatory planning and implementing: utilise participatory research methodologies to facilitate community engagement and tailor interventions; develop tools and governance structures to support learning, teamwork and sustainability; strengthen capacity for participation and collaboration with space for dialogue and shared learning; undertake participatory planning to develop action plans; advocate for implementation; monitor action plans; review and act on successes and challenges; apply community evaluation to understand challenges and enablers and disseminate policy and programme changes. Conclusions: PAR in disease programmes can support health systems to embed cyclical and iterative learning to sustainably address localised equity challenges. However, it takes time, resources and political commitment.